Challenges Confronting Postgraduate Supervision at the National University of Lesotho: : Supervisors’ Perspectives - Tlali, Tebello; Chere-Masopha, Julia; Sebatane, Edith; Khalanyane, Tankie (International Journal of African Higher Education, 2022)
Postgraduate supervision can be a challenging form of teaching, with the challenges further compounded by context or institutional-specific factors.The Faculty of Education at the National University of Lesotho has faced numerous challenges in offering postgraduate degrees, with a few qualified supervisors for the large number of students who enroll in these programmes. This study explored the nature of the challenges confronting postgraduate supervision in this context. It was underpinned by the interpretivist paradigm and employed a qualitative approach. Fifteen supervisors participated, of whom nine (three associate professors and six senior lecturers) were individually interviewed. Six junior lecturers took part in a focus group discussion. Guidelines on postgraduate supervision were also subjected to document review. The findings revealed that while some supervisors had positive experiences, others are frustrated. This is due to a lack of training, and lack of clarity on supervisory procedures, as well as the low academic literacy and lack of commitment exhibited by some students. It is recommended that supervisors should be capacitated through training. Furthermore, supervisory guidelines should be reviewed and benchmarked against best practices in the field. Key words: Postgraduate supervision, constructivism, reflective practice, supervisory guidelines, challenges in supervisory practice